2021
DOI: 10.1186/s12940-021-00781-4
|View full text |Cite
|
Sign up to set email alerts
|

Human detection thresholds of DC, AC, and hybrid electric fields: a double-blind study

Abstract: Background In the course of the ongoing transition of electric energy systems, transmission corridors are often upgraded to higher voltages and other technologies leading to another quality of human exposure. The study aims to determine human detection thresholds for direct current (DC), alternating current (AC), and hybrid electric fields (various DC; constant AC). Methods A total of 203 participants were exposed to DC, AC, and hybrid electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 20 publications
4
20
3
Order By: Relevance
“…This process of AC EF perception is thought to be facilitated by an increased relative permittivity of body hair 7 . Interestingly, in a recent study, we found that higher skin moisture did not result in facilitated EF perception, at least when it was assessed at a single measurement point before starting the EF perception testing 8 . Moreover, body surface sensibility seems to be another important factor influencing EF perception.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…This process of AC EF perception is thought to be facilitated by an increased relative permittivity of body hair 7 . Interestingly, in a recent study, we found that higher skin moisture did not result in facilitated EF perception, at least when it was assessed at a single measurement point before starting the EF perception testing 8 . Moreover, body surface sensibility seems to be another important factor influencing EF perception.…”
Section: Introductionmentioning
confidence: 69%
“…Moreover, body surface sensibility seems to be another important factor influencing EF perception. Kursawe et al recently demonstrated a relationship between vibrotactile measures (31 Hz and 63 Hz) and the detection of AC EFs and hybrid EFs 8 . The authors explained the correlation with hybrid EFs by the kind of evoked sensation, i.e., tingling, itching, or vibration and stressed the importance of body surface sensibility in the interaction mechanism of EF perception 8 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations